Teaching as a lifelong learning: EFL teachers’ perceptions (Concept : Community Concern for English Pedagogy and Teaching, 2020)
The belief and value of teaching as a lifelong learning has long rooted in educational environment. Indonesian context is no exception. Despite of that emerging phenomenon, yet, there are only few evidences that can depict on how such point of view is constructed among EFL teachers in Indonesian context. This study was aimed to investigate EFL teachers’ perception towards teaching as a lifelong learning and to depict the factors that contribute to shape it. This study employed qualitative approach with a case study design. The participant involved were 16 EFL teachers from five different schools in West Java, Indonesia. The data were collected by using questionnaires and interviews. This study used several dependent variables on philosophical of teaching and lifelong learning in order to describe the component that arised from the data collection. The results showed that firstly teachers do believe that learning is inseparable from their identity and profession as educators. Secondly, external factors such as societal and governmental expectation and value have contributively shaped teachers’ belief in teaching as lifelong learning.Key words: EFL Teachers’ perception; Teaching, Lifelong Learning